If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(3x + 6) = -189 Reorder the terms: 7(6 + 3x) = -189 (6 * 7 + 3x * 7) = -189 (42 + 21x) = -189 Solving 42 + 21x = -189 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-42' to each side of the equation. 42 + -42 + 21x = -189 + -42 Combine like terms: 42 + -42 = 0 0 + 21x = -189 + -42 21x = -189 + -42 Combine like terms: -189 + -42 = -231 21x = -231 Divide each side by '21'. x = -11 Simplifying x = -11
| 5/2=9 | | 2n^3+4n^2-7and-n^3+8n-9= | | 3+2y=32 | | 6-(1x+10)=42 | | 10s= | | 6(8-t)+11=-11(t-4)-7 | | 15-x=6x | | 4x^2+7x-92=0 | | 4-4x^2-4y^2+8xy=0 | | 5s= | | 8x+3y=80 | | 2/7k-3/7=-19/8 | | -7y+13=223 | | 5+2y=48 | | 8x+5=8x-6 | | 8.9x+9-1.9x=2 | | 1/8x-2 | | p(3p+1)(3p-1)= | | 55+(2x-49)+90+x=180 | | 13c+40=ac-20+c | | 3x-(4x+9)=5x-45 | | 15x-13=9x-6 | | 8x-3=5+44 | | 2x^2-3x-170= | | 2x-49+55-90+x=180 | | 2w+2*(5+w)=150 | | 6+4[5-3(7+2)-6]= | | 7(2m-2)+2m+10= | | -47-(-95)= | | 2x-49+55=180 | | 2w+10=20 | | 54l+43.42=3605.26 |